Establishment of Organoids From Human Epithelioid Sarcoma With the Air-Liquid Interface Organoid Cultures - Wakamatsu, Toru; Ogawa, Hisataka; Yoshida, Keiichi; Matsuoka, Yukiko; Shizuma, Kazuko; Imura, Yoshinori; Tamiya, Hironari; Nakai, Sho; Yagi, Toshinari; Nagata, Shigenori; Yui, Yoshihiro; Sasagawa, Satoru; et al. (Frontiers in Oncology, 2022)
Background Although biological resources are essential for basic and preclinical research in the oncological field, those of sarcoma are not sufficient for rapid development of the treatment. So far, some sarcoma cell lines have been established, however, the success rate was low and the established sarcoma types were frequently biased. Therefore, an efficient culture method is needed to determine the various types of sarcomas. Organoid culture is a 3-dimentional culture method that enables the recapitulation of the tumor microenvironment and the success rate reported is higher than the 2-dimentional culture. The purpose of this study was to report our newly established organoids from human epithelioid sarcoma using the air-liquid interface organoid culture method. Methods We treated 2 patients with epithelioid sarcoma in our institute. The remaining sarcoma specimens after surgical resection were embedded in collagen type 1 gels according to the air-liquid interface organoid culture method. After serial passages, we xenografted the organoids to NOD-scid IL2Rgnull (NSG) mice. Using the developed tumors, we performed histological and genomic analyses to compare the similarities and differences with the original epithelioid sarcoma from the patient. Results Organoids from the epithelioid sarcoma could be serially cultured and maintained in collagen type 1 gels for more than 3 passages. Developed orthotopic tumor xenografts were detected in the NSG mice. After the process was repeated severally, the patient derived organoid lines from the epithelioid sarcoma were established. The established organoids showed loss of integrase interactor 1 expression with polymerase chain reaction and immunohistochemical analyses. The xenografted organoids of the epithelioid sarcoma had histologically similar phenotypes with the original tumor and genetically resembled it to some degree. Conclusions The present study demonstrated 2 novel established organoid models of epithelioid sarcoma, and our organoid models could be used to investigate the molecular pathogenesis and develop a novel treatment.